Using the Theoretical Domains Framework to identify barriers and facilitators to exercise among older adults living with HIV. Issue 2 (1st February 2019) - Quigley, Adria; Baxter, Larry; Keeler, Laura; MacKay-Lyons, Marilyn
ABSTRACT: People with HIV are living longer. However, co-morbidities are often more prevalent and severe than in the general population and have greater impacts on health status. Although compelling evidence exists about the health benefits of exercise in the HIV literature, many people living with HIV tend to be physically inactive. The purpose of this study was to use the Theoretical Domains Framework to investigate the barriers and facilitators to participation in exercise of older people living with HIV. This qualitative study involved in-depth, semi-structured interviews with 12 adults aged 45 years and older recruited from HIV organizations and health centres. Data were analyzed thematically using the Theoretical Domains Framework, and two investigators independently coded transcripts. Six prominent domains were identified from the interviews: Social influences, environmental context and resources, reinforcement, intentions, social and professional role, and knowledge. Themes emerging from the interviews fit into all 14 domains of the Theoretical Domains Framework, and 67% of themes fit into the six most prominent domains. The participants had a working knowledge of exercise and its health benefits but were unfamiliar with specific exercise parameters. The majority identified environmental or resource constraints as salient barriers for participation in exercise programmes. Co-morbidities, injuries, and the side effects of HIV disease and medication were also acknowledged as barriers. Stigma and discrimination from friends, family, people within the LGBTQ community, and health care providers were commonly discussed. Participants spoke of the importance of social support to facilitate participation in exercise programmes. Other facilitators included using technology and incorporating exercise into day-to-day activities. People aging with HIV experience many barriers to exercise. Those designing exercise interventions for people aging with HIV should incorporate strategies to address these obstacles.